CARA BERTAHAN HIDUP KELUARGA BURUH BANGUNAN (STUDI KASUS DI KELURAHAN PASIR PENGARAIAN) - Sari, Melda; ", Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Writing a thesis entitled "How to Life Survive of Building Worker Family (A Case Study in PasirPengaraian Urban Village)”. In Pasir Pengaraian Urban Village we can meet many building worker, a few building up in PasirPengaraianurban village and the entering of building workers from outside PasirPengaraian urban village make the high competition among thebuilding workers then difficult to get a job, the difficulty of getting a job make the unstable economy of building workers' families. The formulation of the problem (1) How to survive by the family of building workers in the face of economic pressure (2) What factors cause the building worker stay afloat in this work.This research uses descriptive qualitative research method. The results of the research obtained, that the way survival of the building workers family in PasirPengaraianurban village to fulfil the necessities of their family by active way, passive way and the network way.The active way isby doing other work such as working on rubber, harvesting palm oil, fishing, making wreaths and being a driver, another way that the family of building workers is involved or the work other family membersto fulfil the necessities of their families. The passive way that building workers do by saving to buy clothing and other saving such as in the sick the building workerchoose to buy drugs in small store. While the network way is by borrowing the money to another building workers, relatives, neighbors, cooperatives when need urgent money and owed to a stall to fulfil the necessities of their family.Factors of building workers still survive work as a construction or building worker is the absence of ability or skill, income factor, the factor of work experience, and then the comfortable factor.Keywords: Survive, Worker